On starting to teach using CI. Issue 39 (2019) - Ramahlo, Michelle
Abstract : According to Second Language Acquisition (SLA) theory, developed by Stephen Krashen, the way humans acquire languages is through receiving input, usually aural, that is understandable; this is termed 'Comprehensible Input' (CI). Think, for example, of a parent talking to their child: when they ask the child, 'Do you want milk?', the milk is visible, tangible. The child understands that they are being offered milk. Parents don't just say this once, they offer it hundreds, even thousands of times. According to this hypothesis, the input (the parent talking) is comprehensible (the child understands it); the brain is trained to automatically make meaning.